Evaluation of the Home Economics Education graduate programs in Central and Northern Mindanao - Viloria, Tessie G.; Orlina, Elsa A. (2008)
This study evaluated the Home Economics Education (HEED) graduate programs of the State Colleges and Universities (SUCs) in Central and Northern Mindanao based on Context, Input, Process and Product (CIPP). Different questionnaire respective of factors of evaluation were administered to 21 students, 13 graduates, eight faculty, 16 Immediate Supervisors and 28 graduates' peers for a total of 88 respondents. The programs' philosophy, feedback from students and graduates were drawn for the context evaluation. Input evaluation made use of AACCUP and CHED Standards with 10 and six areas of concerns, respectively. The faculty work performance and program management performance level were determined for process evaluation. Product evaluation dealt on the work performance and involvement in various functions of graduates. Documentary analysis was done and was supplemented by observations and interviews. Through the Statistical Package for Social Sciences (SPSS), data were processed using T-Test and Analysis of Variance (ANOVA) to measure differences on perceptions and Chi-square Test to measure relationship among variables. Findings showed that programs have philosophies anchored on HEED, students' and graduates' feedback showed that programs are still wanting of improvement though generally, findings revealed that all factors of the programs were described "Very Good". No difference found in terms of input as to type respondents and institutions, regardless of standards used but an association manifested as to type of institution with the perceived work performance of faculty and graduates on process and products, respectively.
Keywords: Home economics education; Educational evaluation